2012
DOI: 10.1371/journal.pone.0049496
|View full text |Cite
|
Sign up to set email alerts
|

17-AAG Kills Intracellular Leishmania amazonensis while Reducing Inflammatory Responses in Infected Macrophages

Abstract: BackgroundLeishmaniasis is a neglected endemic disease with a broad spectrum of clinical manifestations. Pentavalent antimonials have been the treatment of choice for the past 70 years and, due to the emergence of resistant cases, the efficacy of these drugs has come under scrutiny. Second-line drugs are less efficacious, cause a range of side effects and can be costly. The formulation of new generations of drugs, especially in developing countries, has become mandatory.Methodology/Principal FindingsWe investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 59 publications
6
53
0
Order By: Relevance
“…It remains unclear, why anti-BP IgG-induced IL-6 expression was not hampered in response to Hsp90 inhibition in our study, although NFκB is also known to be an important transcription factor for this cytokine and impairment of the inflammatory IL-6 pathway by Hsp90 blockade was previously demonstrated in various cell types (except keratinocytes) (Sato et al 2003;Wax et al 2003;Mitsiades et al 2006;Lang et al 2007;Ambade et al 2012;Petersen et al 2012;Shimp et al 2012a, b). Similar to our study, however, inhibition of NFκB by Bay-11-7082 suppressed the upregulation of different proinflammatory cytokines, but also did not compromise the IL-6 response in diaphragm muscle cells exposed to oxidative stress (Sigala et al 2011).…”
Section: Discussionmentioning
confidence: 54%
“…It remains unclear, why anti-BP IgG-induced IL-6 expression was not hampered in response to Hsp90 inhibition in our study, although NFκB is also known to be an important transcription factor for this cytokine and impairment of the inflammatory IL-6 pathway by Hsp90 blockade was previously demonstrated in various cell types (except keratinocytes) (Sato et al 2003;Wax et al 2003;Mitsiades et al 2006;Lang et al 2007;Ambade et al 2012;Petersen et al 2012;Shimp et al 2012a, b). Similar to our study, however, inhibition of NFκB by Bay-11-7082 suppressed the upregulation of different proinflammatory cytokines, but also did not compromise the IL-6 response in diaphragm muscle cells exposed to oxidative stress (Sigala et al 2011).…”
Section: Discussionmentioning
confidence: 54%
“…The presence and importance of Hsp90 in trypanosomatids has been shown [3][6]. However little is known about the Hsp90 co-chaperones, including their in vivo presence and roles.…”
Section: Resultsmentioning
confidence: 99%
“…TEM evaluation of L. donovaniinfected mouse PMFs actually revealed an increased proportion of membranous vesicle homing to parasite-containing vacuoles upon Wnt5a pretreatment. TEM also demonstrated that these macrophages exhibit an increased proportion of PVs bearing a degradation phenotype characterized by the presence of laminated structures (39), as well as an overall diminished abundance of PVs. These findings are represented in Fig.…”
Section: Wnt5a-rac1/rho Gtpase-mediated Altered Cytoskeletal Dynamicsmentioning
confidence: 91%